DEVELOPMENT AND TESTING OF A COMPUTER MODEL TO SIMULATE WATER TABLE RESPONSE TO SUBIRRIGATION - ROSA, JADIR APARECIDO; Smajstrla, Allen George; Campbell, Kenneth Leonard (IRRIGA, 2002)
DEVELOPMENT AND TESTING OF A COMPUTER MODEL TO SIMULATE WATER TABLE RESPONSE TO SUBIRRIGATION Jadir Aparecido Rosa Pólo Regional de Ponta Grossa, Instituto Agronômico do Paraná , Caixa Postal 129, CEP 84001-970, Ponta Grossa – PR, E-mail: jrosa@pr.gov.br Allen George Smajstrla (deceased) Kenneth Leonard Campbell Agricultural and Biological Engineering Department, University of Florida, PO Box 110570, Gainesville - Florida, 36511-0570 USA, E-mail: klc@agen.ufl.edu 1 ABSTRACT A two-dimensional finite difference model (WATABLE) was developed to simulate water movement from a buried microirrigation line source, and the response of the water table to irrigation, precipitation, evapotranspiration, deep percolation, and runoff. The water uptake by plant roots was simulated by an extraction function with a root distribution term. Deep percolation was modeled with a water table-drainage flux relationship, and runoff was simulated at the surface and at the face of the water furrow. The accuracy of the model in simulating infiltration and redistribution of soil water was determined by comparison with other computer simulations and experimental observations from the literature. The comparisons were selected to test the applicability and accuracy of the model with soils that had widely varying hydraulic properties. Results from WATABLE agreed very well with other simulation models and the model was able to reproduce closely the experimental results taken for comparison. This article focuses on the development and testing of the simulation model and a further article will present the calibration and verification of the model comparing results with experimental observations on water table management research plots. KEYWORDS: drainage, modeling, subsurface drip irrigation. ROSA, J.A., SMAJSTRLA, A.G., CAMPBELL, K.L. DESENVOLVIMENTO E TESTE DE UM MODELO COMPUTACIONAL PARA SIMULAR A RESPOSTA DO LENÇOL FREÁTICO À SUBIRRIGAÇÃO 2 RESUMO Um modelo computacional em duas dimensões (WATABLE) foi desenvolvido para simular o movimento de água a partir de uma linha de irrigação localizada enterrada, e a resposta do nível do lençol à irrigação, precipitação, evapotranspiração, percolação profunda e escorrimento superficial. O consumo de água pelas raízes foi simulado com uma função de extração e um termo de distribuição de raízes. A percolação profunda foi modelada através de uma relação entre profundidade do lençol e fluxo de drenagem na parte inferior do perfil. A precisão do modelo na simulação da infiltração e da redistribuição da água no solo foi determinada comparando-se resultados obtidos com este modelo e simulações feitas com outros modelos e dados experimentais obtidos na literatura. As comparações foram selecionadas de modo a testar a aplicabilidade e precisão do modelo em diferentes tipos de solos. Os resultados obtidos com o WATABLE foram concordantes com aqueles obtidos com outros modelos, e o modelo foi capaz de reproduzir muito bem os resultados experimentais tomados como referências. Este artigo apresenta o desenvolvimento e os testes de simulação com o modelo, e um futuro artigo apresentará os resultados da calibração e verificação do modelo usando-se dados de campo obtidos em uma área experimental em manejo de lençol freático. UNITERMOS: drenagem, modelagem, irrigação por subsuperfície.